Ministers and Masters : Methodism, Manhood, and Honor in the Old South - Carney, Charity R., 1982- (Book collections on Project MUSE., 2011)
In Ministers and Masters Charity R. Carney presents a thorough account of how Methodist preachers constructed their own concept of masculinity within and at times in defiance of the constraints of southern honor culture of the early nineteenth century. By focusing on this unique subgroup of southern men, the book explores often-debated concepts like southern honor and patriarchy in a new way.